Potential of hybrids among elite clones of eucalypt by microsatellite markers - Aguiar, Marcelo Sfeir de; Ferreira, Daniel Furtado; Aguiar, Aurélio Mendes; Bison, Odair; Rezende, Gabriel Dehon Sampaio Peçanha; Grattapaglia, Dario (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the potential of microsatellite markers to predict the performance of hybrids among elite clones of eucalypt from Aracruz Celulose. Twenty one elite clones were crossed in a full-diallel mating scheme. One hundred and thirty seven hybrids, 21 parents and 11 repeated hybrids were evaluated in three sites: Aracruz, São Mateus and Caravelas, in an experimental design of incomplete blocks 13x13 with 40 replicates, comprising single plant plot and spaced 3x3 m. The characters evaluated were the circumference at breast height (CBH) and the wood basic density, two years after the planting. Means were submitted to diallel analysis and, later, the correlation between the genetic divergence of parents by microsatellite markers and the estimative of diallel parameters were obtained. The genetic divergence was correlated with the specific combining ability to CBH height and with the means of hybrids to the same character. The other coefficients of correlation with the genetic divergence were not significantly different from zero. The prediction by microsatellite markers is of little accuracy to be utilized in place of diallel estimates.